2015
DOI: 10.4236/ajps.2015.68122
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Fingerprinting of <i>Camelina</i> Species Using cTBP as Molecular Marker

Abstract: Interest on the genus Camelina has recently increased due to the biofuel, or jet fuel, potential of the oil extracted from seeds of the cultivated species Camelina sativa (L.) Crantz. While our knowledge on C. sativa is constantly augmenting, only few studies have been performed on the other species of the genus, which could be a potentially useful material for the genetic improvement of C. sativa. The genus Camelina consists of 11 species, but only six (C. sativa, C. microcarpa, C. alyssum, C. rumelica, C. hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 30 publications
0
20
0
4
Order By: Relevance
“…For instance, no significant difference was observed for oil content between the HG-240 C. hispida accession and C. sativa accessions (Appendix 7.5). Galasso et al (2015) also observed high genetic variability within C. hispida accessions relative to the other Camelina species perhaps indicating that this species may be a predecessor for subsequent polyploid species within the genus. In this case, we hypothesize that the parental ancestors of C. sativa may be the result of a hybridization event between C. hispida (n = 7) and the diploid C. microcarpa (n = 6) or C. laxa (n = 6) due to its basal chromosome numbers of 7+7+6 (Kagale et al, 2014).…”
Section: Understanding Genetics Of Natural (Phenotypic) Variation In mentioning
confidence: 84%
See 4 more Smart Citations
“…For instance, no significant difference was observed for oil content between the HG-240 C. hispida accession and C. sativa accessions (Appendix 7.5). Galasso et al (2015) also observed high genetic variability within C. hispida accessions relative to the other Camelina species perhaps indicating that this species may be a predecessor for subsequent polyploid species within the genus. In this case, we hypothesize that the parental ancestors of C. sativa may be the result of a hybridization event between C. hispida (n = 7) and the diploid C. microcarpa (n = 6) or C. laxa (n = 6) due to its basal chromosome numbers of 7+7+6 (Kagale et al, 2014).…”
Section: Understanding Genetics Of Natural (Phenotypic) Variation In mentioning
confidence: 84%
“…microcarpa and Camelina species in general. A chromosome count of 2n = 26 has been reported for C. rumelica indicating a tetraploid status for this species (Galasso et al, 2015;Martin et al, 2016). Diploid counts of 2n = 14 were reported for C. hispida which has been consistent across several studies (Al-Shehbaz, 1987;Hutcheon et al, 2010;Galasso et al, 2015;Martin et al, 2016) whereas diploid counts of 2n = 12 were reported for C. laxa (Galasso et al, 2015;Martin et al, 2016).…”
Section: The Camelina Genusmentioning
confidence: 89%
See 3 more Smart Citations